Very Low Ventricular Pacing Rates Can Be Achieved Safely in a Heterogeneous Pacemaker Population and Provide Clinical Benefits: The CANadian Multi‐Centre Randomised Study‐Spontaneous AtrioVEntricular Conduction pReservation (CAN‐SAVE R) Trial. Issue 7 (July 2015) - Thibault, Bernard; Ducharme, Anique; Baranchuk, Adrian; Dubuc, Marc; Dyrda, Katia; Guerra, Peter G.; Macle, Laurent; Mondésert, Blandine; Rivard, Léna; Roy, Denis; Talajic, Mario; Andrade, Jason; et al.
Abstract : Background: It is well recognized that right ventricular apical pacing can have deleterious effects on ventricular function. We performed a head‐to‐head comparison of the SafeR pacing algorithm versus DDD pacing with a long atrioventricular delay in a heterogeneous population of patients with dual‐chamber pacemakers. Methods and Results: In a multicenter prospective double‐blinded randomized trial conducted at 10 centers in Canada, 373 patients, age 71±11 years, with indications for dual chamber DC pacemakers were randomized 1:1 to SafeR or DDD pacing with a long atrioventricular delay (250 ms). The primary objective was twofold: (1) reduction in the proportion of ventricular paced beats at 1 year; and (2) impact on atrial fibrillation burden at 3 years, defined as the ratio between cumulative duration of mode‐switches divided by follow‐up time. Statistical significance of both co‐primary end points was required for the trial to be considered positive. At 1 year of follow‐up, the median proportion of ventricular‐paced beats was 4.0% with DDD versus 0% with SafeR ( P <0.001). At 3 years of follow‐up, the atrial fibrillation burden was not significantly reduced with SafeR versus DDD (median 0.00%, interquartile range [0.00% to 0.23%] versus median 0.01%, interquartile range [0.00% to 0.44%], respectively, P =0.178]), despite a persistent reduction in the median proportion of ventricular‐paced beats (10% with DDD compared to 0% with SafeR). Conclusions: A ventricular‐paced rate <1% was safely achieved with SafeR in a population with a wide spectrum of indications for dual‐chamber pacing. However, the lower percentage of ventricular pacing did not translate into a significant reduction in atrial fibrillation burden. Clinical Trial Registration: URL:https://www.clinicaltrials.gov/ Unique identifier: NCT01219621.